Carbonates and Evaporites - Carbonates and Evaporites (Springer Nature, 2026)
Carbonates and Evaporites is a specialized journal focused on all aspects of carbonate and evaporite geology: Provides a platform for the exchange of ideas through professional papers, reports, and letters to the editor; Features relevant news from societies and a regular book review section; Offers valuable content for professionals and students in geological fields; Fosters a comprehensive understanding of carbonate and evaporite rocks and their associated phenomena.
FI 0.59
Q3
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Acuerdos transformativos; Transformative agreements; Geoquímica de carbonatos; Procesos evaporíticos; Facies sedimentarias; Estratigrafía